The clinical use of circulating tumor cells (CTCs) enumeration for staging of metastatic breast cancer (MBC): International expert consensus paper. (February 2019) - Cristofanilli, Massimo; Pierga, Jean-Yves; Reuben, James; Rademaker, Alfred; Davis, Andrew A.; Peeters, Dieter J.; Fehm, Tanja; Nolé, Franco; Gisbert-Criado, Rafael; Mavroudis, Dimitrios; Grisanti, Salvatore; Giuliano, Mario; et al.
Abstract: Background: The heterogeneity of metastatic breast cancer (MBC) necessitates novel biomarkers allowing stratification of patients for treatment selection and drug development. We propose to use the prognostic utility of circulating tumor cells (CTCs) for stratification of patients with stage IV disease. Methods: In a retrospective, pooled analysis of individual patient data from 18 cohorts, including 2436 MBC patients, a CTC threshold of 5 cells per 7.5 ml was used for stratification based on molecular subtypes, disease location, and prior treatments. Patients with ≥ 5 CTCs were classified as Stage IVaggressive, those with < 5 CTCs as Stage IVindolent. Survival was analyzed using Kaplan-Meier curves and the log rank test. Results: For all patients, Stage IVindolent patients had longer median overall survival than those with Stage IVaggressive (36.3 months vs. 16.0 months, P < 0.0001) and similarly for de novo MBC patients (41.4 months Stage IVindolent vs. 18.7 months Stage IVaggressive, p < 0.0001). Moreover, patients with Stage IVindolent disease had significantly longer overall survival across all disease subtypes compared to the aggressive cohort: hormone receptor-positive (44 months vs. 17.3 months, P < 0.0001), HER2-positive (36.7 months vs. 20.4 months, P < 0.0001), and triple negative (23.8 months vs. 9.0 months, P < 0.0001). Similar results were obtained regardless of prior treatment or disease location. Conclusions: We confirm the identification of two subgroups of MBC, Stage IVindolent and Stage IVaggressive, independent of clinical and molecular variables. Thus, CTC count should be considered an important tool for staging of advanced disease and for disease stratification in prospective clinical trials.